Preliminary Radiographic Classification of First Metatarsal Osteotomy Healing Following Minimally Invasive Hallux Valgus Surgery - Thomas L. Lewis MBChB(Hons), BSc(Hons), FRCS(Tr&Orth), MFSTEd; Sanjana Mehrotra; Jonathan Kaplan MD; Tyler Gonzalez MD, MBA; Sergio Morales MD, MSc; Thomas J. Goff MBChB, FRCS(Tr&Orth), PGDip; Vikramman Vignaraja MBBS, BSc(Hons); Ayla Claire Newton MBBS, MA(Cantab), AFHEA, MRCS; Robbie Ray MBChB, ChM(T&O), FRCSEd(Tr&Orth), FEBOT; Peter Lam MBBS(Hons), FRACS (Foot & Ankle Orthopaedics)
Background: Minimally invasive or percutaneous surgery (MIS) for hallux valgus correction has seen increased adoption because of a growing evidence base of positive clinical and radiographic outcomes following surgery. However, no standardized or validated radiographic classification exists to evaluate the first metatarsal osteotomy healing following MIS hallux valgus surgery. The aim was to develop a new radiographic classification system for assessing bone healing following MIS distal transverse osteotomy for hallux valgus. Methods: A 4-domain radiographic classification system based on callus formation, anteroposterior (AP) osteotomy line, lateral osteotomy line, and remodeling for MIS osteotomy healing was developed and tested on a cohort of 27 feet that underwent percutaneous transverse osteotomy for hallux valgus correction. Patients had simultaneous postoperative weightbearing computed tomography (WBCT) and standard radiographs following surgery. Five surgeons reviewed anonymized radiographs to evaluate interobserver reliability. WBCT was used to confirm union status and classification interpretation. Results: The classification system demonstrated substantial interobserver reliability for lateral osteotomy line (Fleiss kappa = 0.671, 95% CI 0.505-0.814) and AP osteotomy line assessment (Fleiss kappa = 0.664, 95% CI 0.459-0.811), with moderate agreement for callus formation (κ = 0.465) and remodeling (κ = 0.439). The classification showed strong correlation with WBCT findings, with an optimal threshold of 8 points identified to differentiate union from nonunion, achieving an overall classification accuracy of 85.2%. This finding was supported by the area under the receiver operating characteristic (ROC) curve of 0.832. At the optimal threshold, the classification demonstrated 90.0% sensitivity and 71.4% specificity for detecting union. Conclusion: This preliminary classification provides a reliable tool for assessing first metatarsal bone healing following MIS hallux valgus osteotomies, with substantial interobserver reliability. It offers a standardized approach for radiographic evaluation, which may enhance comparability across studies and serve as a radiographic research tool pending further validation. Its clinical applicability remains to be determined. Level of Evidence: Level III, diagnostic study.